Microbiome and Resistome Studies of the Lithuanian Baltic Sea Coast and the Curonian Lagoon Waters and Sediments - Greta Gyraitė; Marija Kataržytė; Rafael Picazo Espinosa; Greta Kalvaitienė; Eglė Lastauskienė (MDPI AG, 2024)
Background: the widespread use of antibiotics in human and veterinary medicine has contributed to the global challenge of antimicrobial resistance, posing significant environmental and public health risks. Objectives: this study aimed to examine the microbiome and resistome dynamics across a salinity gradient, analyzing water and sediment samples from the Baltic Sea coast and the Curonian Lagoon between 2017 and 2023. Methods: the composition of the water and sediment bacterial community was determined by Full-Length Amplicon Metagenomics Sequencing, while ARG detection and quantification were performed using the SmartChipTM Real-Time PCR system. Results: the observed differences in bacterial community composition between the Baltic Sea coast and the Curonian Lagoon were driven by variations in salinity and chlorophyll a (chl a) concentration. The genera associated with infectious potential were observed in higher abundances in sediment than in water samples. Over 300 genes encoding antibiotic resistance (ARGs), such as aminoglycosides, beta-lactams, and multidrug resistance genes, were identified. Of particular interest were those ARGs that have previously been detected in pathogens and those currently classified as a potential future threat. Furthermore, our findings reveal a higher abundance and a distinct profile of ARGs in sediment samples from the lagoon compared to water. Conclusions: these results suggest that transitional waters such as lagoons may serve as reservoirs for ARGs, and might be influenced by anthropogenic pressures and natural processes such as salinity fluctuation and nutrient cycling.